Evaluación de la vía shamanga – balbanera del cantón colta de 2.6 km de longitud - Torres Alvarez, Christian Xavier (2012)
In the province of Chimborazo, the rural areas are generally poor, they do not often have adequate road networks that will allow them to commercialize their agricultural and livestock products, these roads have been built without any design criteria, as a consequence of this, there are some tracing errors. In this research project the constructed road will be analyzed and evaluated in order to execute the geometric design based on the standards set by the MTOP (Ministry of Transport and Public Works) of the Shamanga - Balbanera road located in the Colta canton.